678. Outbreak of Shiga Toxin-Producing Escherichia coli Infections at Marine Corps Recruit Depot (MCRD), San Diego and Camp Pendleton, California: October–November, 2017. (26th November 2018) - Keaton, Amelia; Hassan, Rashida; Luna, Sarah; Lee, Isabell; Magalhaes, Richelle; Bidlack, Matthew; Graf, Paul; Maves, Ryan; Smith, Linda; Freer, Douglas; Flinn, Kimberly; Monk, Gregory; et al.
Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) infections are a major cause of foodborne illness and the principal cause of hemolytic-uremic syndrome (HUS). In November 2017, CDC and the US Navy responded to an outbreak of STEC illnesses in military recruits at the Marine Corps Recruit Depot in San Diego (MCRD). We investigated to determine the source of this outbreak and identify prevention and mitigation measures. Methods: In October 2017, medical staff identified a high number of gastrointestinal (GI) illnesses at MCRD. Recruits with diarrhea submitted stool specimens for culture and/or culture-independent diagnostic testing (CIDT) for GI pathogens. We performed pulsed-field gel electrophoresis (PFGE) on culture isolates. Case-patients were defined as confirmed (PFGE-confirmed STEC infection matching outbreak strains), probable (diagnosis of HUS and/or CIDT evidence of STEC), or suspected (bloody diarrhea). We conducted environmental evaluations of dining facilities, training areas, and barracks. A case–control study was performed using PFGE-confirmed case-patients and platoon-matched controls. We performed product traceback for foods identified as exposure risks by interview or case–control study. Results: We identified 64 confirmed, 105 probable, and 91 suspected case-patients. Thirty case-patients required hospitalization and 15 had HUS. Ages ranged from 17 to 28 years (median: 18 years). Poor hygiene practices among recruits and inconsistent cooking temperatures within dining facilities were noted. Forty-three case-patients and 135 controls were interviewed about food, hygiene, and environmental exposures. Consumption of undercooked beef was significantly associated with illness (mOR 2.40, CI 1.04–5.72, P = 0.04). We identified a single ground beef supplier for MCRD, but dining facility records did not document the dates on which specific lots of ground beef were used. Conclusion: Case–control analysis and environmental observations suggested undercooked ground beef as a potential source for this outbreak. We recommended the Navy and Marine Corps retain lot information, address food handling concerns, and improve hygiene among recruits. Disclosures: All authors: No reported disclosures.